2014
DOI: 10.1186/1746-160x-10-7
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effects of functional orthodontic appliances on cervical spine posture: a retrospective cephalometric study

Abstract: IntroductionInteractions between the cervical spine and the stomatognathic system have been discussed in literature. The present study was conducted to investigate whether, and to what extent, orthodontically induced mandibular advancement produces changes in cervical spine posture. Furthermore, possible appliance-specific effects should be distinguished.Material and methodsThe cephalograms of 64 patients with skeletal class II were analysed before and after mandibular advancement. Linear and angular cephalome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…The cervical lordosis angle increased in the study group at the end of treatment, probably due to a significant backward inclination of the upper segment of the cervical column, but there was no significant change in the lower segment of the cervical column inclination [ 19 ]. Concordant with the present study results, Ohnmeis et al, in a retrospective cephalometric study, concluded that the cervical spine was straighter after orthodontic treatment with functional appliances, but they suggested that such straightening could be a result of physiological growth [ 21 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The cervical lordosis angle increased in the study group at the end of treatment, probably due to a significant backward inclination of the upper segment of the cervical column, but there was no significant change in the lower segment of the cervical column inclination [ 19 ]. Concordant with the present study results, Ohnmeis et al, in a retrospective cephalometric study, concluded that the cervical spine was straighter after orthodontic treatment with functional appliances, but they suggested that such straightening could be a result of physiological growth [ 21 ].…”
Section: Discussionsupporting
confidence: 90%
“…However, the results from available studies are very controversial. Furthermore, only a few studies have evaluated changes in cervical posture during orthodontic treatment with functional appliances [ 19 , 21 ]. Aggarwal et al established a significant increase in postural and maximal clenching EMG activity in masseter and a numeric but not significant increase in anterior temporalis activity during the 6-month period of treatment with the Twin-block; they stated that functional appliances are shown to modify the neuromuscular environment of the dentition and associated bones.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed a significant difference between the PF1 and PF2 SNB, ANB, and OPT/CVT angles, indicating an improvement in sagittal relationships and an increase in cervical curvature. Ohnmeiß et al 24 also found a significant difference between the PF1 and PF2 ANB values. Similarly, a significant difference in the SNB and ANB angles in PF1 and PF2 indicated an improvement in the sagittal relationships in this study.…”
Section: Discussionmentioning
confidence: 87%
“…The mean values of the mandibular plane angle in the exposed group indicate that a majority of the subjects had a normal vertical growth pattern, therefore no significant differences were noted in the PF1 and PF2 cervical parameters. Whereas Agalrci 23 found a significant difference between the OPT-CVT angles, indicating a change in the middle cervical posture, Ohnmeiß et al 24 did not find a significant difference between the cervical parameters. We found a significant difference in the mean change of the SN-OPT angle, which can be interpreted as an uprighting of the upper cervical posture.…”
Section: Discussionmentioning
confidence: 91%
“…[7][8][9][10] In our study, the twin-block helped upright the cervical posture as it has been seen to do so in various other studies. 11,12 Mandibular advancement appliances improve upper airway dimensions and should thereby reduce the hyperflexion of the cervical spine. 13 Technological advancements such as cone-beam computed tomography are of greater value in diagnosing airway impairment compared with lateral cephalograms.…”
mentioning
confidence: 99%